Extended-spectrum and Metallo-beta lactamase enzymes mediated resistance in Pseudomonas aeruginosa in clinically isolated specimens - Farooq Ali; Seema Kamal; Qismat Shakeela; Shehzad Ahmed (Kuwait Journal of Science)
Pseudomonas aeruginosa is one of the leading opportunistic pathogens, frequently highlighted for the production of ESBL and MBL enzymes. This is believed to be the primary inhabitant of soil due to its adaptive nature and can survive in aquatic and even in toxic environment. The current study was aimed to screen ESBL and MBL producing and MDR strains of P. aeruginosa. Clinical specimens collected from patients and were screened for the presence of P. aeruginosa. After identification, all the isolates were tested for the sensitivity pattern following Kirby-Bauer disc diffusion method. The presence of ESBL and MBL enzymes were detected following DDST and IMP-EDTA detection tests respectively. Totally 1369 clinical specimens were collected, among which 126 (9.20%) specimens grown the colonies of P. aeruginosa on culture media. 54.76% (69/126) of the positive specimens confirmed in female population, whereas, 45.24% (57/126) in male population. High frequency rate, (n=43/126) was detected in age group ≥31 year, followed by 21-30 (n=35/126), and 11-20 (n=34/126) age group, the minimal frequency (n=14/126) was detected in age group 0-14. The sensitivity pattern showed that majority of the isolates were resistant, but class carbapenem, aminoglycosides and some other antibiotics i.e. sulbactam-Cefoperazone, tazobactam-piperacillin, tigecycline and Fosfomycin showed best results to P. aeruginosa. it is concluded that the emergence of resistance due to ESBL and MBL enzymes in P. aeruginosa is directly linked with public health concern because these strains are almost resistant to a wide range of antibiotics and only limited antibiotics are potent against these organisms.